A model of Service-Oriented Architecture and firm/network performance. (2nd December 2009) - Chen, Andrew N.K.; Nichols, Jason
In this paper, we seek to lay a foundation for the analysis of the relationships between SOA and previously discovered antecedents to organisational performance. We review the fundamentals of SOA and the literature regarding IT and firm performance, and we present a research model for examining the impact of SOA and other firm's resources/capabilities on the performance of a firm and a value network. Our analysis and propositions provide guidelines for future research and knowledge advancement in the area of SOA and IT business value.